2019
DOI: 10.1007/s12020-019-02145-y
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-infiltrating cytotoxic T lymphocytes in somatotroph pituitary neuroendocrine tumours

Abstract: Introduction Somatotroph pituitary tumours are often resistant to first-generation somatostatin analogues and can invade the surrounding structures, limiting the chances of curative surgery. Recent studies suggested that the immune microenvironment and pro-angiogenic factors can influence neuroendocrine tumour prognosis. In this study, we aimed to investigate the prognostic role of immune cell-specific markers and endocan, a proteoglycan involved in neoangiogenesis and cell adhesion, in a cohort of acromegaly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 45 publications
5
20
1
Order By: Relevance
“…Instead, we found that the tumor size and patient age presented different correlations with the distribution of TIICs, mostly neutrophils and T cells. Some of these results are novel to those of previous studies ( 13 , 18 , 19 , 58 ).…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Instead, we found that the tumor size and patient age presented different correlations with the distribution of TIICs, mostly neutrophils and T cells. Some of these results are novel to those of previous studies ( 13 , 18 , 19 , 58 ).…”
Section: Discussionmentioning
confidence: 46%
“…An improved understanding of the immune characteristics of the TME and novel classifications based on different immune features might provide insights into the mechanisms of different immunotherapy responses and serve as resources for future targeted studies ( 16 , 17 ). Several studies have investigated intratumoral T-cell infiltration and programmed death-ligand 1 (PD-L1) expression in PAs ( 13 , 18 , 19 ). Iacovazzo et al ( 19 ) demonstrated that a lower number of CD8 + T cells is related to both the invasion of PAs to the cavernous sinus and resistance to treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, in another study only endothelial endocan expression correlated with tumor size and recurrence, both signs of aggressiveness, and no correlation with invasion was found (17). Similarly, no relation of endocan and cavernous sinus invasion or resistance to treatment with rst-generation somatostatin analogues was found in acromegaly patients (39), though endocan may participate in the resistance of prolactinomas to dopamine therapy (34).…”
Section: Discussionmentioning
confidence: 93%
“…In the PA stroma, CD68+ macrophages > CD4+ T cells and CD8+ T cells. [ 31 , 41 , 47 , 48 , 51 53 ] 35; 134; 28;35; 64; 115; 15 Immunohistochemistry; Computational approach; flow cytometry 2021; 2020; 2020; 2015; 2020; 2020; 2019 CD147 Invasion tumors > non-invasive tumors. [ 55 ] 55 Immunohistochemistry 2005 CD163 The most abundant type of immune cell in PitNETs, and mainly CD163 +.…”
Section: Immune Cells Infiltrate In Pasmentioning
confidence: 99%